The pygmy mole crickets (Orthoptera: Tridactylidae) of Florida, USA, with descriptions of three new species - Woo, Brandon (Zootaxa, 2025)
The results of an intensive survey of Florida (U.S.A.) Pygmy Mole Crickets (Orthoptera: Tridactylidae) are presented. Six members of the family have been previously recorded from the state. This work describes three additional species and documents additional locality records for the other taxa, bringing the Florida total to nine species. Two-thirds of these species are narrowly endemic to small ranges within the state and are restricted to xeric sandhill or scrub habitats with bare patches of sand. Distributional patterns as well as conservation implications for the endemic species are discussed.